Association of light emitting diodes (LED) devices with premature aging: a cross-sectional descriptive study - Sadia Rehman; Owais Saeed, Shaikh Muhammad; Shariff, Yumna; Muhammad Raza Sarfraz; Khan, Seemab; Sami, Zara (Journal of the Pakistan Medical Association, 2026)
Objective: To assess the relationship between light-emitting diode device usage and premature aging. Method: The cross-sectional, descriptive study was conducted from October 2023 to May 2024 after approval from the ethics review committee of Pakistan Naval Ship Shifa Hospital, Karachi, and comprised individuals aged 27-40 years. Other than demographic characteristics, data was collected about light-emitting diode device usage and indicators of premature aging based on self-reported and observed features. Data was analysed using SPSS 29. Results: Of the 450 participants with mean age 32.4±3.7 years, 225(50%) each were males and females. Commonly used devices were mobile phones 400(88.9%), television 350(77.8%) and laptops 300(66.7%). Overall, 200(44.4%) subjects reported 5-7 hours of screen time, and 300(66.7%) did not use ultraviolet protection. Devices were used at a distance of 10-20cm by 200(44.4%) subjects. In terms of premature aging signs, the most common was dark circles 325(72.2%), while greying of hair was the least common 200(44.4%). All aging variables showed a highly significant association with light-emitting diode usage (p<0.01), with the exception of greying of hair which demonstrated a significant association but at a lower level (p<0.05). Conclusion: There was a significant link between light-emitting diode device usage and premature aging. Key Words: Light-emitting diode, Premature aging, Screen time.